Budget Management at the Department of Education and Culture of Central Maluku District - Dewi Tuasikal; I. H. Wenno; S. Rumfot (Peneliti.net, 2023)
This study aims (1) to analyze the budget for educational facilities and infrastructure in Central Maluku Regency. (2) to analyze the distribution of teachers based on the budget in Central Maluku Regency. (3) to analyze the supporting and inhibiting factors of facility problems. educational infrastructure in Central Maluku District and (4) Analyze the supporting and inhibiting factors for the distribution of teachers in Central Maluku District. This type of research is qualitative descriptive research. The research subjects are informants. The selected informants were the Head of the Education and Culture Office, the Head of General Affairs and Personnel Subdivision, the Head of Sub-Finance, the Head of PAUD and PNF, the Head of PTK, Planning Staff, and the sub-district coordinator in Central Maluku Regency who could provide information relevant to the focus of this research. The object of research is the Education Budget 2021 at the Central Maluku Regency Education and Culture Office, Infrastructure Data, Good Schools, Teacher Data, Number of Classes, and Number of Schools. The techniques used in data collection include direct observation. documentation, interviews, and observations. The results of the study show that: (1) The Education Budget for Infrastructure Facilities for the Education and Culture Office of Central Maluku Regency has been cut in 2021 but the budget has not decreased but has increased, this shows that the Central and Regional governments always prioritize budgets on things that are considered urgent to implement. (2) The Education Budget for Equalizing Teachers in Central Maluku Regency which is earmarked by the government for teacher professional allowances, special teacher allowances, and additional income sourced from the State Revenue and Expenditure Budget (APBN) is one of the priority programs, so that even though there are budget cuts, funds for allowances teachers cannot be reduced in the amount of the budget. (3) Inhibiting Factors and Problems with Infrastructure, namely budget constraints, geographical conditions, and natural damage, while supporting factors are government commitment, potential natural resources, and financial support from the government (4) Inhibiting Factors with teacher distribution problems at the Education and Culture Office of Central Maluku Regency are budget constraints, remote areas, and social problems. The supporting factors are government programs, improving infrastructure in remote areas, and improving the quality of teachers